2021
DOI: 10.3390/catal11050550
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Co Incorporation on the CO Oxidation Activity of LaFe1−xCoxO3 Perovskites

Abstract: Perovskite oxides are versatile materials due to their wide variety of compositions offering promising catalytic properties, especially in oxidation reactions. In the presented study, LaFe1−xCoxO3 perovskites were synthesized by hydroxycarbonate precursor co-precipitation and thermal decomposition thereof. Precursor and calcined materials were studied by scanning electron microscopy (SEM), attenuated total reflection Fourier transform infrared spectroscopy (ATR-FTIR), thermogravimetric analysis (TG), and X-ray… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 21 publications
(56 citation statements)
references
References 60 publications
13
43
0
Order By: Relevance
“…Within the phase-pure orthorhombic perovskites, a volcano-like behavior was observed with a maximum of 15 % Co, which might be superimposed to the composition effect in both channels. A similar non-linear activity increase was reported before in CO oxidation and exhaust gas decomposition on LaFe x Co 1À x O 3 , [19,50] Co-doped NiO in CO oxidation, [51] and LaFeO 3 with Co and Sr doping. [23] For all catalysts, acetone was the main product.…”
Section: The Effect Of B-cation Substitution On Dry Feed Selective 2-propanol Oxidationsupporting
confidence: 88%
See 1 more Smart Citation
“…Within the phase-pure orthorhombic perovskites, a volcano-like behavior was observed with a maximum of 15 % Co, which might be superimposed to the composition effect in both channels. A similar non-linear activity increase was reported before in CO oxidation and exhaust gas decomposition on LaFe x Co 1À x O 3 , [19,50] Co-doped NiO in CO oxidation, [51] and LaFeO 3 with Co and Sr doping. [23] For all catalysts, acetone was the main product.…”
Section: The Effect Of B-cation Substitution On Dry Feed Selective 2-propanol Oxidationsupporting
confidence: 88%
“…As reported in our previous study, the (112) reflection shifted to higher angles, indicating the incorporation of the smaller Co 3 + cations into the perovskite lattice. [19,30] For x � 0.40, no phase pure materials were synthesized. Instead, a mixture of three crystalline phases was observed.…”
Section: Synthesis and Materials Characterizationmentioning
confidence: 99%
“…[63,64] The smallest fraction of the total phase composition was made up of the spinel phase, [61] which might derive from phase segregation in the precursor state where a layered double hydroxide is formed in the otherwise amorphous precursor at higher Co contents, presumably [a] The values for materials with x = 0-0.30 had been reported previously. [52,59] ChemElectroChem consisting mainly of Fe and Co which means the two elements segregate from La. [61] Thus, a too high degree of segregation in the precursor state causes the formation of the spinel phase in the calcined materials.…”
Section: Resultsmentioning
confidence: 99%
“…A suitable candidate class of materials for anodic reactions in water electrolysis are perovskites, [12,[51][52][53][54][55][56][57][58] metal oxides with the general formula ABO 3 consisting typically of rare-earth metals on the A-site, and transition metals on the B-site. The latter directly affects their electrocatalytic properties and changes therein may impact the reaction mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Catalytic oxidation in several temperature cycles is frequently used in the literature to show catalyst stability [18,19]. However, some studies indicated further effects of either pretreatment or subsequently performed catalytic runs.…”
Section: Introductionmentioning
confidence: 99%